Rethinking reappraisal: Insights from affective neuroscience. (2nd September 2015) - Grecucci, Alessandro; Job, Remo
Abstract: Kalisch et al. argue that appraisal and reappraisal are key mechanisms promoting resilience; however, experimental findings seem to contradict this simplistic view. We argue that a deeper look at affective neuroscience may provide complementary and stronger evidence on how emotional reactivity and emotion regulation may affect resilience.